29 Achieving meaningful heart failure readmission reductions in a safety net hospital. (25th November 2019) - Whalen, Deborah; Awtry, Eric; Carey, Ann; Caruso, Lisa; Gauthier, Diane; Gopal, Deepa; Lincoln, Nicole; Paul, Ludwine; Johnstone, Donald; Plummer, Jennifer; Saraf, Christine; Yurkovic, Alexandra
Abstract : Background: Heart Failure (HF) the most frequent MS-DRG resulting in 30 day readmission is a major focus of readmission reduction initiatives. Achieving meaningful and sustained reductions in HF readmissions in a Safety Net Hospital is particularly challenging. Boston Medical Center achieved this goal through designing a robust slate of multidisciplinary interventions tapping existing institutional resources in new ways. Objectives: Design a slate of multidisciplinary interventions that lower BMC's average 30 day Medicare HF readmission to less than 19% by May 2019. Methods: Using PDSA methodology a multidisciplinary team implemented interventions addressing care processes, co-morbidities and social determinants of health. Effectiveness was monitored through automated performance dashboards. Interventions included (1) Inpatient HF Consult Criteria patients not on Cardiology teams; (2) Standardized RN Teach Back and EPIC smart phrases discharge documentation; (3) VNA support HF home discharges, preferential respite admission when homelessness; (4) HF Clinic Nurse Practitioner follow up appointments within 7–14 days discharge ;(5) Scripted call day prior Cardiology appointment to mitigate barriers to arrival;(6) Concurrent Renal consultation CKD IV or V patients not on hemodialysis. Results: In the six month prior to QI initiative, BMC's Medicare 30 day HF readmission rate averaged 26.85% which decreased to 15.2% (12/1/18–6/30/19) as the slate of interventions fully activated. Total HF readmissions showed similar decrease from 23.9% to 17.2%. Conclusions: BMC demonstrates that meaningful Heart Failure readmission reductions can be achieved Safety Net Hospitals by tapping into existing institutional resources in new ways. Planning permanent accountable team, automated dashboards and robust feedback loops insure reductions seen are sustained.